2020
DOI: 10.17219/acem/115238
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation in interstitial lung diseases: A review of the literature

Abstract: There are more than 200 different diseases classed as interstitial lung diseases (ILDs). For epidemiological and practical purposes, ILDs are classified into diseases of known and unknown etiology. The aim of this review is to evaluate our current knowledge about the efficacy and safety of pulmonary rehabilitation (PR) in patients with ILDs. Other issues, such as ILD pathogenesis, prevalence and comorbidity, are also elaborated in the review. Pulmonary rehabilitation is an important part of comprehensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…In our study, QoL was assessed using the SF-36, and there was an improvement in QoL after 6 weeks of respiratory rehabilitation, which was statistically significant with the control group. Studies have found that: respiratory rehabilitation can improve the QoL of patients with COPD [6], asthma [13], lung cancer after surgery [14]. Additionally, we found that 6 weeks of respiratory rehabilitation significantly improved anxiety in elderly patients with COVID-19, which is consistent with the effect of respiratory rehabilitation in COPD with Rebelo [15].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, QoL was assessed using the SF-36, and there was an improvement in QoL after 6 weeks of respiratory rehabilitation, which was statistically significant with the control group. Studies have found that: respiratory rehabilitation can improve the QoL of patients with COPD [6], asthma [13], lung cancer after surgery [14]. Additionally, we found that 6 weeks of respiratory rehabilitation significantly improved anxiety in elderly patients with COVID-19, which is consistent with the effect of respiratory rehabilitation in COPD with Rebelo [15].…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that people with ILD may need more careful planning and modification of their exercise prescription than healthy subjects or even patients with COPD 24 . Compared with the number of studies including COPD patients, clinical studies dealing with pulmonary rehabilitation in ILD are relatively small 33 . Principles of pulmonary rehabilitation are similar for both groups of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Principles of pulmonary rehabilitation are similar for both groups of diseases. However, exercise‐induced desaturation and related complications occur more frequently in ILD patients, emphasizing the importance of proper training intensity selections 33 …”
Section: Discussionmentioning
confidence: 99%
“…На любом из этапов реабилитационных мероприятий важнейшую роль играет выполнение специальных дыхательных упражнений [3][4][5]. Кроме того, большое значение имеет применение физических методов лечения, в том числе различных видов электромагнитной стимуляции или магнитотерапии [6].…”
Section: список сокращенийunclassified